2024
DOI: 10.1021/jacsau.3c00703
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure to Tailor the Electrochemical Behavior of Mixed-Valence Copper Sulfides during Water Electrolysis

Avinava Kundu,
Biswarup Chakraborty

Abstract: The semiconducting behavior of mixed-valence copper sulfides arises from the pronounced covalency of Cu–S bonds and the exchange coupling between CuI and CuII centers. Although electrocatalytic study with digenite Cu9S5 and covellite CuS has been performed earlier, detailed redox chemistry and its interpretation through lattice structure analysis have never been realized. Herein, nanostructured Cu9S5 and CuS are prepared and used as electrode materials to study their electrochemistry. Powder X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…S10†) to achieve 10 mA cm −2 current density, without much change in the catalytic actvity. 57 In comparison, the Bi 3 O 4 Br/NF anode only reached 50 mA cm −2 current density at 1.72 V, which indicated an enhanced OER activity presumably due to the active contribution of Mn-doping in Bi 3 O 4 Br. The use of a different Mn II and Bi III precursor ratio (see the Experimental section) during synthesis gave a very similar polycrystalline (with a notable amorphous feature) Mn-doped Bi 3 O 4 Br material (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…S10†) to achieve 10 mA cm −2 current density, without much change in the catalytic actvity. 57 In comparison, the Bi 3 O 4 Br/NF anode only reached 50 mA cm −2 current density at 1.72 V, which indicated an enhanced OER activity presumably due to the active contribution of Mn-doping in Bi 3 O 4 Br. The use of a different Mn II and Bi III precursor ratio (see the Experimental section) during synthesis gave a very similar polycrystalline (with a notable amorphous feature) Mn-doped Bi 3 O 4 Br material (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Bi 3 O 4 Br and Mn–Bi 3 O 4 Br were initially deposited on the GC electrode to perform the OER under alkaline conditions (1 M KOH). 57 Cyclic voltammetry (CV) cycles were recorded within 0.9–1.9 V ( vs . RHE) in a three-electrode system, using materials deposited on GC, Pt wire and Hg/HgO as working (WE), counter (CE) and reference electrode (RE), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Kundu et al , in a recent investigation, achieved tailoring of the electrochemical behavior of mixed valent copper sulfide nanomaterials during water electrolysis. 55 They also correlated the device performance to the atomic arrangements and coordination geometry of the surface exposed sites. Liu et al studied these Cu vacancies within the crystal lattices of metal deficient copper sulfides and concluded that the phenomenon enhances their performance in photodetectors or solar cells.…”
Section: Resultsmentioning
confidence: 99%